Evaluación de las propiedades estructurales, morfológicas y magnéticas del sistema Bi1-xSmxFeO3 - Betancourt-Montañez, Iván Fernando; Varela-Olivera, Christian Fabian; Munevar-Cagigas, Julian Andres; Sandoval-Gutiérrez, Santiago; Ortíz-Otálora, César Armando; Parra-Vargas, Carlos Arturo; Sánchez Sáenz, Claudia Liliana (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
This paper reports the synthesis of the Bi1-xSmxFeO3 system (x = 0.00, 0.02, 0.04, 0.06, 0.08 and 0.10) obtained by thesolid-state reaction method at 1073.15 K for 15 h. Characterization allowed evaluating the effect of Sm3+ insertion on thestructural, morphological and magnetic properties of the bismuth ferrite. Structural characterization was made by X-rayDiffraction (XRD) and Rietveld refinement, indicating the formation of a rhombohedral majority phase of the space groupR3c (161) with a proportion higher than the reported up to now. The morphological characterization through scanning electron microscopy (SEM) allowed concluding that the insertion of samarium decreases the particle size from 7.5 μm to 2.5 μm, thanks to the smaller ionic radius, which also led to the contraction of the lattice parameters. The magnetic analysis showed a typical ferromagnetic behaviour in all of the synthesized samples, with the presence of a PM-AFM transition at 260 K.